Exploring the unseen: Unleashing the potential of Synthesia AI in pedagogical approaches / Ts. Jacqueline Joseph - Joseph, Jacqueline (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The rapid development of AI, or artificial intelligence, in recent years is reshaping the way people interact with machines. Synthesis AI is an advanced innovation that utilizes AI and deep learning algorithms to create educational videos with a humanlike voice actor. This technology offers educators, trainers, and corporations the opportunity to deliver highly tailored and engaging learning experiences remotely. Synthesia AI accomplishes its tasks by analyzing data from text, audio, and video using sophisticated natural language techniques. Incorporating demographic information of the learners into the creation of a video's simulated human speaker's appearance, voice, and vocabulary can enhance accessibility and interest in the content. Subsequently, a script for the digital speaker is generated based on the analysis of user-entered instructional text. Utilizing facial recognition technology, the AI produces a video that seamlessly matches the script. One of Synthesia AI's key selling points is its ability to generate unique and captivating lesson plans.